Localisation in PET images: direct fitting of the intercommissural (AC-PC) line. - Friston, K; Passingham, R; Nutt, J; Heather, J; Sawle, G; Frackowiak, R (1989)
A technique is described for estimating the position of the intercommisural line (AC-PC line) directly from landmarks on positron emission tomographic (PET) images, namely the ventral aspects of the anterior and posterior corpus callosum, the thalamus, and occipital pole. The relationship of this estimate to the true AC-PC line, fitted through the centres of the anterior and posterior commissures, showed minimal vertical and angular displacement when measured on magnetic resonance imaging (MRI) scans. Using regression analysis, the ease and reliability of fitting to these points was found to be high. This directly derived AC-PC line estimate was validated in terms of the assumptions used in the method of Fox et al. The ratio of distance between the AC-PC line and a line passing through the base of the inion (GI line) to total brain height was 0.21, as predicted. The technique has been further validated by localizing focal activation of the sensorimotor cortex. The technique is discussed in terms of absolute limits to localization of structures in the brain using noninvasive tomographic techniques in general and PET in particular.